Minimalist Wardrobe for Elderly Inspired by Dupli Casa, Germany - Azmi, Syazwani; Selimin, Mohamad Ali; Chumiran, Mohd Hasni (Research in Management of Technology and Business, 2022)
Malaysia’s senior population increased during the third and fourth quarters of 2018. The growing old population is regarded as an ageing problem that is not limited to Malaysia but is a worldwide issue. Existing furniture nowadays may have a detrimental influence on elderly health since they have movement limitations owing to their body flexibility. For instance, almost 89.6% of the older populations were dissatisfied with the current wardrobe design. Therefore, the purpose of this study is to design and develop a prototype of a minimalist wardrobe for the elderly inspired by Dupli Casa, Germany. A Google Form survey was distributed to persons who live with older people or who may have an opinion regarding geriatric-friendly design. The survey data was used in the design and prototyping processes. In this study, two visuals research, two thumbnails, four ideations, seven idea developments, and a final design were generated based on the obtained design criteria. According to the results of the survey, the wardrobe design should include a hanging area, stacking space, and drawers. The majority of respondents also requested to have a sensor light in the wardrobe as an added feature. This wardrobe’s prototype is built of plywood and laminated plywood. In addition, the wardrobe’s door is made of a hinged door, which allows the elderly to have a better view of the inside. The newly designed wardrobe in this study is intended to ensure that senior individuals, even if they live alone, have no difficulty utilising and organising their wardrobes.